A comparison of computational models for wrinkling of pressurized shell-core systems. (December 2020) - Veldin, Tomo; Lavrenčič, Marko; Brank, Boštjan; Brojan, Miha
Abstract: Four nonlinear computational models for the surface wrinkling of curved shell-core systems under external pressure are presented. Three of the considered finite element models neglect the displacements tangential to the shell surface. Two of the models are static formulations and the other two are derived in the dynamic framework. For the latter, the energy-decaying time-stepping algorithm is applied, which is suitable for numerically stiff problems, such as shell-core systems, characterized by stiff membrane and soft wrinkling deformation modes. In all cases the core is modeled by elastic springs. As a comparative problem we choose the surface wrinkling of pressurized shell-core spheres. In particular, five systems with different material and geometric properties are computed, which have different wrinkle patterns. A good agreement is found between the results of the models as well as with the relevant references, which provide numerical and experimental results. However, it has been observed that our reduced-order models are blind to the prediction of the secondary transformation – from the dimple-like pattern to the labyrinthine pattern. Another conclusion is that a non-tailored (i.e. standard) shell finite element on an elastic foundation combined with the energy-decaying scheme, provides excellent predictions of the surface wrinkle patterns. Highlights: Four nonlinear FE models for wrinkling of curved shell-core systems are presented. For comparison of the models a spherical shell-core system is chosen. Two static and two dynamic models are used to predict the surface pattern. Isolated dimple, multiple dimple, labyrinthine and mixed modes are predicted.